PENGARUH TAX AVOIDANCE, INTELLECTUAL CAPITAL, EARNING MANAGEMENT TERHADAP FIRM VALUE (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BEI TAHUN 2020-2024) - Indi Lestiawati; Sunarto (Jurnal Nusa Akuntansi, 2026)
This study aims to determine and obtain empirical evidence of the influence of Tax Avoidance, Intellectual Capital, and Earnings Management on company value in the energy sector during the observation period of 2020-2024. The dependent variable in this study is company value, while the independent variables in this study are Tax Avoidance, Intellectual Capital, and Earnings Management. This study is quantitative and uses an associative method and data sourced from the annual reports of energy sector companies for the period 2020-2024 with panel data regression analysis techniques. The results of the study in the form of a Tax Avoidance and Earning Management variables do not affect Company value while the Intellectual Capital variable does affect Company Value.